Volar Dislocation of the Fourth and Fifth Carpometacarpal Joints: A Case Report and Review of the Literature - Prokopis, Peter M. (Springer-Verlag, 2008)
We report the treatment of a volar dislocation to the fourth and fifth carpometacarpal (CMC) joints. Plain radiographs were used to evaluate this unusual injury before surgery. Open reduction and internal fixation using K-wires restored the normal anatomic relationships of the CMC joints. This very rare injury is often difficult to recognize. A careful neurologic assessment of the patient is a necessity, as well as obtaining proper radiographs of the hand. A review of the literature is presented.